Multi‐band bisected Hilbert monopole antenna loaded with multiple subwavelength split‐ring resonators. Issue 10 (11th May 2018) - Goswami, Chiranjib; Ghatak, Rowdra; Poddar, Dipak R.
Abstract : Here, a simple yet effective design methodology to design multi‐band planar antenna is proposed. The monopole antenna structure is realised using a bisected fractal Hilbert curve. Two subwavelength split‐ring resonators (SRRs), where one is a Moore shaped fractal SRR, operates at 3.5 GHz, and the other conventional one operates at 5.2 GHz, are placed in proximity to the compact monopole to achieve two additional operating bands apart from the two resonant frequencies of the fractal‐shaped monopole. The third and fourth bands are merged to obtain wide impedance bandwidth around 5.5 GHz. The proposed antenna displays tri‐band resonance that covers 2.4 GHz WLAN band, 3.5 GHz Wi‐MAX band, and the wide band ranges from 5.0 to 6.15 GHz. Stable monopole‐like pattern over all the bands is observed. The overall antenna dimension is 33 × 20 × 0.787 mm 3 . A fabricated prototype is developed that exhibits good agreement between the measurement and simulation results.